Giant cystic pheochromocytoma a case report - Minei, S (Hinyokika kiyo. Acta urologica Japonica, 2001)
The patient, a 59-year-old woman, was referred to our University Hospital for evaluation of a left mass. Ultrasonography revealed a left adrenal cystic mass. On excretory urograms, the left kidney was pressed downward by a suprarenal mass, and computerized tomography (CT) and magnetic resonance imaging (MRI) confirmed an adrenal cyst. 131I-meta-iodo-benzylguanidine (MIBG) scintigraphy showed prominent accumulation in the left adrenal mass and the capsule. Considering the elevation of catecholamines in both blood and urine samples, we performed a left adrenalectomy with a presumptive diagnosis of pheochromocytoma (tumor size: 11.6 x 7.5 x 6.5 cm, tumor weight 720 g). The subsequent pathological examination confirmed a left giant cystic pheochromocytoma. 131I-MIBG scintigraphy was the most useful tool in the diagnosis of the cystic pheochromocytoma